A computational study of cellulose regeneration: All-atom molecular dynamics simulations. (1st July 2023) - Heasman, Patrick; Mehandzhiyski, Aleksandar Y.; Ghosh, Sarbani; Zozoulenko, Igor
Abstract: Processing natural cellulose requires its dissolution and regeneration. It is known that the crystallinity of regenerated cellulose does not match that of native cellulose, and the physical and mechanical properties of regenerated cellulose can vary dependent on the technique applied. In this paper, we performed all-atom molecular dynamics simulations attempting to simulate the regeneration of order in cellulose. Cellulose chains display an affinity to align with one another on the nanosecond scale; single chains quickly form clusters, and clusters then interact to form a larger unit, but the end results still lack that abundance of order. Where aggregation of cellulose chains occurs, there is some resemblance of the 1–10 surfaces found in Cellulose II, with certain indication of 110 surface formation. Concentration and simulation temperature show an increase of aggregation, yet it appears that time is the major factor in reclaiming the order of "crystalline" cellulose. Graphical abstract: Unlabelled Image